FARDHU KIFAYAH (Sebuah Analisa Pemikiran Hukum Prof. K.H. Ali Yafie) - Sadat, Anwar (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2011)
This article describes the problem Fardhu kifayah: An Analysis of Legal Thought Prof. K.H. Ali Yafie in which try to explain the concept of Fardhu kifayah once again placing it a more proportional. In this study the authors also try to provide a more solid description set out in the discussion with an intellectual biography of a charismatic cleric in South Sulawesi. The method used in this study pure library approach is to read various scientific works, especially leaders KH Ali Yafie. The results showed fardhu kifaya concept is a concept that is very rational in growing social concern for> people with fixed based on what the writer is term prudence in religion.